Species of Odontosyllis Claparède, 1863 (Annelida: Polychaeta: Syllidae) - Fukuda, Marcelo Veronesi; Nogueira, João Miguel De Matos; Paresque, Karla; Martín, Guillermo San (Zootaxa, 2013)
Two new species of Odontosyllis were found in samples collected mainly on rocky shores off the states of São Paulo (SE Brazil) and Paraíba (NE Brazil). Odontosyllis aracaensis sp. nov., and O. guarauensis sp. nov., are herein described and compared to their most similar congeners. A key for the species found in Brazil is provided, and relevant morphological characters of similar species of the genus, based on falcigers morphology, are summarized and compared with those of the newly described species. The current state of knowledge on the genus is briefly discussed.